Antihyperalgesic Activities of Endocannabinoids in a Mouse Model of Antiretroviral-Induced Neuropathic Pain - Munawar, Neha; Oriowo, Mabayoje A.; Masocha, Willias (Frontiers in Pharmacology, 2017)
Background: Nucleoside reverse transcriptase inhibitors (NRTIs) are the cornerstone of the antiretroviral therapy for HIV/AIDS. However, their use is sometimes limited by the development of a painful sensory neuropathy, which does not respond well to drugs. Smoked cannabis has been reported in clinical trials to have efficacy in relieving painful HIV-associated sensory neuropathy. Objectives: The aim of this study was to evaluate whether the expression of endocannabinoid system molecules is altered during NRTI-induced painful neuropathy, and also whether endocannabinoids can attenuate NRTI-induced painful neuropathy. Methods: BALB/c mice were treated with 25 mg/kg of 2′,3′-dideoxycytidine (ddC, zalcitabine), a NRTI, to induce thermal hyperalgesia. The expression of endocannabinoid system molecules was evaluated by real time PCR in the brain, spinal cord and paw skin at 6 days post ddC administration, a time point when mice had developed thermal hyperalgesia. The effects of the endocannabinoids, N-arachidonoyl ethanolamine (AEA) and 2-arachidonoyl glycerol (2-AG), the cannabinoid type 1 (CB1) receptor antagonist AM 251, CB2 receptor antagonist AM 630, and G protein-coupled receptor 55 (GPR55) antagonists ML193 and CID 16020046 on ddC-induced thermal hyperalgesia were evaluated using the hot plate test. Results: ddC treatment resulted in thermal hyperalgesia and increased transcripts of the synthesizing enzyme Plcβ1 and decreased Daglβ in the paw skins, but not Napepld, and Daglα compared to vehicle treatment. Transcripts of the inactivating enzymes Faah and Mgll were downregulated in the brain and/or paw skin but not in the spinal cord of ddC-treated mice. Both AEA and 2-AG had antihyperalgesic effects in mice with ddC-induced thermal hyperalgesia, but had no effect in ddC-naïve mice. The antihyperalgesic activity of AEA was antagonized by AM251 and AM630, whereas the activity of 2-AG was antagonized by AM251, ML193 and CID 16020046, but not by AM630. Conclusions: These data show that ddC induces thermal hyperalgesia, which is associated with dysregulation of the mRNA expression of some endocannabinoid system molecules. The endocannabinoids AEA and 2-AG have antihyperalgesic activity, which is dependent on cannabinoid receptor and GPR55 activation. Thus, agonists of cannabinoid receptors and GPR55 could be useful therapeutic agents for the management of NRTI-induced painful sensory neuropathy.